Community Empowerment Efforts Through the Kampung Kita Kampung Tematik Program (Case Study: Mangga Village, Tangerang City) - Lestari, Mulyani; Fadil, Cholid; Imaningsih, Niniek (Unram Journal of Community Service, 2025)
Kampung Kita Kampung Tematik Program is a program of the local government of Tangerang City to alleviate slum areas and empower the community through the utilization of regional potential. The Kampung Kita Thematic Village Program aims to create a creative, innovative, and harmonious community through economic, environmental, and social approaches based on the characteristics of each village area. This research examines what stages are carried out before the implementation of the program by highlighting the planning stage and what programs are contained in Kampung Mangga. Based on the results of interviews conducted in Kampung Mangga in Tangerang City, the community felt the positive impact of the Kampung Kita Thematic Village program because it could increase community participation in several activities in the village. The results of the interviews showed that this program succeeded in increasing community participation in environmental development, strengthening community harmony, and creating new economic opportunities through the management of educational tourism.